Performance Comparison of High Strength Reinforced Concrete Circular and Square Columns Subjected to Flexural Controlled Cyclic Loading - Ali Ahmed; Ahmed Mohammed Youssef Mohammed; Koichi Maekawa (Salehan Institute of Higher Education, 2021)
In existing design practices selection of circular or square column shape mostly depends upon architectural needs rather than structural behavior. The behavior of equivalent area (circular and square), high strength reinforced concrete columns is reported to be same under monotonic loading conditions but their behavior under fatigue loading is not well-established. This paper presents the comparison of high strength reinforced concrete circular and square equivalent area columns’ performance (load-deflection behavior) under fatigue loading. Columns were casted in four configurations: square and circular shapes and with and without shear stirrups. Experimental results showed that in case of columns without shear stirrups, the square column resisted 38% more loading cycles as compared to circular column while the maximum deflection was 78% more than the circular column. Similarly, in case of columns with shear stirrups, square shaped column resisted 55% more loading cycles with only 5% more maximum deflections as compared to circular column. The results show that the square columns might be considered more ductile as compared to circular columns under the application of cyclic loading conditions like wind forces or seismic forces. Therefore, it might be concluded that square columns should be recommended for highly seismic regions as compared to circular columns with equivalent area. Doi: 10.28991/cej-2021-03091639 Full Text: PDF